2016
DOI: 10.1371/journal.pone.0159637
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Sevoflurane Causes Rho-Dependent Filopodial Shortening in Mouse Neurons

Abstract: Early postnatal anesthesia causes long-lasting learning and memory impairment in rodents, however, evidence for a specific neurotoxic effect on early synaptogenesis has not been demonstrated. Drebrin A is an actin binding protein whose localization in dendritic protrusions serves an important role in dendritic spine morphogenesis, and is a marker for early synaptogenesis. We therefore set out to investigate whether clinically-relevant concentrations of anesthetic sevoflurane, widely- used in infants and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
(53 reference statements)
0
22
0
Order By: Relevance
“…In particular, synapsin1, vesicular glutamate transporters (VGluT1), PSD95, and Homer1a are classical markers of presynaptic and postsynaptic proteins, which play an important role in synaptic activity [54][55][56][57][58][59]. Previous research has reported that the repeated sevoflurane exposure downregulates synaptic proteins such as postsynaptic protein PSD95 in the hippocampus of developing mice [60,61]. In the present study, we detect the effect of sevoflurane and resveratrol on the expression of these proteins.…”
Section: Resveratrol Restored Synaptic Protein Expression Ex Vivomentioning
confidence: 61%
“…In particular, synapsin1, vesicular glutamate transporters (VGluT1), PSD95, and Homer1a are classical markers of presynaptic and postsynaptic proteins, which play an important role in synaptic activity [54][55][56][57][58][59]. Previous research has reported that the repeated sevoflurane exposure downregulates synaptic proteins such as postsynaptic protein PSD95 in the hippocampus of developing mice [60,61]. In the present study, we detect the effect of sevoflurane and resveratrol on the expression of these proteins.…”
Section: Resveratrol Restored Synaptic Protein Expression Ex Vivomentioning
confidence: 61%
“…A previous study demonstrated that the anesthetic agent isoflurane destabilizes spine actin, which results in alterations to dendritic spine morphology and number ( 31 ). Zimering et al ( 17 ) additionally observed that sevoflurane causes actin depolymerization, leading to reversible length-shortening of dendritic protrusions through a mechanism involving activation of RhoA/ROCK signaling. Ketamine is commonly used as an intravenous general anesthetic for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has a number of limitations. Exposure to anesthetics transiently affects the dynamics of dendritic spines, and dendritic protrusion loss and shrinkage are reversible ( 17 , 31 , 38 ). The present study was based on single time-point observations; it is not known whether ketamine-induced effects on the morphology and number of dendritic spines may be attenuated upon ketamine elimination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations